Enhanced electrochemical decontamination and water permeation of titanium suboxide reactive electrochemical membrane based on sonoelectrochemistry - Teng, Jie (2021)
Reactive electrochemical membrane (REM) allows electrochemical oxidation (EO) water purification under flow-through operation, which improves mass transfer on the anode surface significantly. However, O2 evolution reaction (OER) may cause oxygen bubbles to be trapped in small-sized confined flow channels, and thus degrade long-term filterability and treatability of REM. In this study, ultrasound (ultrasonic vibrator, 28 kHz, 180 W) was applied to EO system (i. e. sonoelectrochemistry) containing titanium suboxide-REM (TiSO-REM) anode for enhanced oxidation of 4-chlorophenol (4-CP) target pollutant. Both experimental and modeling results demonstrated that ultrasound could mitigate the retention of O2 bubbles in the porous structures by destructing large-size bubbles, thus not only increasing permeate flux but also promoting local mass transfer. Meanwhile, oxidation rate of 4-CP for EO with ultrasound (EO-US, 0.0932 min-1) was 216% higher than that for EO without ultrasound (0.0258 min-1), due to enhanced mass transfer and OH production under the cavitation effect of ultrasound. Density functional theory (DFT) calculations confirmed the most efficient pathway of 4-CP removal to be direct electron transfer of 4-CP to form [4-CP]+, followed by subsequent oxidation mediated by OH produced from anodic water oxidation on TiSO-REM anode. Last, the stability of TiSO-REM could be improved considerably by application of ultrasound, due to alleviation of electrode deactivation and fouling, indicated by cyclic test, scan electron microscopy (SEM) observation and Fourier transform infrared spectroscopy (FT-IR) characterization. This study provides a proof-of-concept demonstration of ultrasound for enhanced EO of recalcitrant organic pollutants by REM anode, making decentralized wastewater treatment more efficient and more reliable.